The HIV-Brazil cohort study: design, methods and participant characteristics. - Alexandre Grangeiro; Maria Mercedes Escuder; Alex Jones Flores Cassenote; Rosa Alencar Souza; Artur O Kalichman; Valdiléa G Veloso; Maria Letícia Rodrigues Ikeda; Maria Letícia Rodrigues Ikeda; Nêmora Tregnago Barcellos; Carlos Brites; Unai Tupinanbás; Noaldo O Lucena; et al. (PLoS ONE)
Background The HIV-Brazil Cohort Study was established to analyze the effectiveness of combination antiretroviral therapy (cART) and the impact of this treatment on morbidity, quality of life (QOL) and mortality. The study design, patients' profiles and characteristics of cART initiation between 2003 and 2010 were described. Methodology/principal findings Since 2003, the HIV-Brazil Cohort has been following HIV-infected adults receiving cART at 26 public health care facilities, using routine clinical care data and self-reported QOL questionnaires. When not otherwise available, data are obtained from national information systems. The main outcomes of interest are diseases related or unrelated to HIV; suppression of viral replication; adverse events; virological, clinical and immunological failures; changes in the cART; and mortality. For the 5,061 patients who started cART between 2003 and 2010, the median follow-up time was 4.1 years (IQR 2.2-5.9 years) with an 83.4% retention rate. Patient profiles were characterized by a predominance of men (male/female ratio 1.7∶1), with a mean age of 36.9 years (SD 9.9 years); 55.2% had been infected with HIV via heterosexual contact. The majority of patients (53.4%) initiated cART with a CD4+ T-cell count ≤200 cells/mm3. The medications most often used in the various treatment regimens were efavirenz (59.7%) and lopinavir/ritonavir (18.2%). The proportion of individuals achieving viral suppression within the first 12 months of cART use was 77.4% (95% CI 76.1-78.6). Nearly half (45.4%) of the patients presented HIV-related clinical manifestations after starting cART, and the AIDS mortality rate was 13.9 per 1,000 person-years. Conclusions/significance Results from cART use in the daily practice of health services remain relatively unknown in low- and middle-income countries, and studies with the characteristics of the HIV-Brazil Cohort contribute to minimizing these shortcomings, given its scope and patient profile, which is similar to that of the AIDS epidemic in the country.